Prediction of TiN coating adhesion strength on aerospace AL7075-T6 alloy using fuzzy rule based system - Zalnezhad, E.; Sarhan, Ahmed Aly Diaa Mohammed; Abd Shukor, Mohd Hamdi (2012)
In this research work, predicting of titanium nitride (TiN) coating adhesion on AL7075-T6 is presented. First TiN was coated on Al7075-T6 in different conditions and the surfaces adhesion of TiN coated specimens were measured using micro scratch force machine. Second a fuzzy logic model was established to predict the of TiN coating adhesion on AL7075-T6 with respect to changes in input process parameters, DC power, DC bias voltage, and nitrogen flow rate based on the tried data obtained from the scratch force test. Four membership functions are allocated to be connected with each input of the model. Third, new five experimental tests were carried out to verify the predicted results achieved via fuzzy logic model. The result indicated settlement between the fuzzy model and experimental results with the 95.534 accuracy.